Efficacy of Art Therapy in the Reduction of Impulsive Behaviors of Children with ADHD Co-Morbid Intellectual Disability - Hina Ayaz Habib, Uzma Ali (Pakistan Journal of Psychology, 2015)
The present study intended to explore the efficacy of art therapy in the reduction of impulsive behaviors of children with Attention Deficit/ Hyperactivity Disorder (ADHD) co-morbid Intellectual Disability (ID) in Karachi, Pakistan. The study was based on experimental design for which the data was collected from different special schools located in Karachi –Pakistan. Sample was selected through purposive sampling of 14 children with ADHD (mild) comorbid Mild ID with age ranging between 6 to 12 years (mean age= 7.391; SD = 1.315) during the year 2011 -2013 belonging to middle socioeconomic status. The sample was divided into two groups, treatment and control group. Treatment group received 25 art as therapy sessions while control group received regular class room activities. Children were placed in the treatment and control group by ABBA technique after 8 hours of observation. Followed by the administration of Demographic Information Sheet, Attention Deficit Hyperactivity Disorder Test (Gilliam, 1995) and Human Figure Drawing (Koppitz, 1968) were administered before and after the therapy sessions. Descriptive statistics and Wilcoxon test were calculated through SPSS version 17.0. Findings suggest that art as therapy is effective in the reduction of impulsive behaviors in children with ADHD co-morbid ID (p<.05). The findings of this research have its clinical implications in multiple disciplines i.e. for psychologist and special educators. Recommendations for future research have also been suggested.